(untitled) (Research, Society and Development, 2026)
The present study aimed to analyze the main risk factors associated with injuries in recreational runners, describe the most commonly reported prevention methods in the scientific literature, and highlight the importance of these strategies for the safe practice of running. This study is a literature review in which databases such as PubMed, SciELO, and PEDro were consulted, using descriptors related to injury prevention and running. Studies published within the last six years that met the established inclusion criteria were selected. The results indicate that the occurrence of injuries is multifactorial, involving the interaction between biomechanical factors, such as movement patterns and motor control, training-related factors, such as load and its progression, and individual characteristics, such as age, body mass, and level of experience. Strategies such as muscle strengthening, gait retraining, the use of feedback, and health education have demonstrated potential in reducing the risk of injuries, especially when applied in a structured and supervised manner. Educational and behavioral interventions showed positive effects, particularly when associated with structured exercise programs, highlighting the importance of integrated approaches.it is concluded that injury prevention in recreational runners should be understood as a complex and multifactorial process that requires the combination of different strategies and consideration of individual characteristics. Physiotherapeutic intervention is essential in the development of effective preventive programs, contributing not only to the reduction of injury incidence but also to the maintenance of sports practice, promoting health and quality of life.